(untitled) (The Review of Diabetic Studies, 2025)
The cardiac catheterization laboratory (Cath Lab) has evolved into a highly specialized, technology-driven environment that requires interdisciplinary collaboration among nurses, cardiovascular technologists, and radiologic professionals. This paper explores the expanding roles of these allied health professionals within the Cath Lab, emphasizing their evolving clinical, technical, and leadership responsibilities. Through a synthesis of recent literature, the study identifies how role expansion enhances procedural efficiency, patient safety, and professional satisfaction. Findings indicate that nurses are increasingly involved in hemodynamic monitoring, sedation management, and patient education, while cardiovascular technologists assume greater responsibility for data analysis, device operation, and quality assurance. Radiologic technologists contribute to image optimization, radiation safety, and hybrid imaging integration. Despite these advancements, challenges persist, including inconsistent credentialing standards, legal restrictions, and institutional resistance to change. The paper concludes that structured competency frameworks, interprofessional education, and policy reforms are essential to support sustainable role expansion. The integration of artificial intelligence, digital health technologies, and advanced practitioner pathways is expected to further redefine collaborative practice. Aligning these developments with initiatives such as Saudi Vision 2030 can strengthen the Cath Lab workforce, enhance healthcare delivery, and promote patient-centered excellence in cardiovascular care.